The 745.5 issue in code‐based, adult congenital heart disease population studies: Relevance to current and future ICD‐9‐CM and ICD‐10‐CM studies. (20th December 2017) - Rodriguez, Fred H.; Ephrem, Georges; Gerardin, Jennifer F.; Raskind‐Hood, Cheryl; Hogue, Carol; Book, Wendy
Abstract: Objective: Although the ICD‐9‐CM code 745.5 is widely used to indicate the presence of a secundum atrial septal defect (ASD), it is also used for patent foramen ovale (PFO) which is a normal variant and for "rule‐out" congenital heart disease (CHD). The ICD‐10‐CM code Q21.1 perpetuates this issue. The objective of this study was to assess whether code 745.5 in isolation or in combination with unspecified CHD codes 746.9 or 746.89 miscodes for CHD, and if true CHD positives decrease with age. Design: Echocardiograms of patients with an ICD‐9‐CM code of 745.5 in isolation or in combination with unspecified CHD codes 746.9 or 746.89 were reviewed to validate the true incidence of an ASD. This observational, cross‐sectional record review included patients between 11 and 64 years of age. Results: Medical charts and echocardiograms of 190 patients (47.9% males) were reviewed. The number of falsely coded patients with 745.5 (no ASD) was high (76.3%). Forty‐five (23.7%) patients had a true ASD. Among the 145 patients without an ASD, 100 (52.6%) were classified as having a PFO, 37 (19.5%) had a normal non‐CHD echocardiogram, and 8 (4.2%) had some other CHD anomaly. The likelihood that 745.5 coded for a true ASD was higher in children aged 11‐20 (64.3%) than adults aged 21‐64 years (20.6%). Conclusions: This validation study demonstrates that 745.5 performed poorly across all ages. As 745.5 is widely used in population‐level investigations and ICD‐10‐CM perpetuates the problem, future analyses utilizing CHD codes should consider separate analysis of those identified only through code 745.5.